Plant breeding reviews. - Janick, Jules, 1931- (Plant Breeding Reviews., 2014)
Plant Breeding Reviews 38 Table of Contents1. Daniel Zohary: Geneticist and Explorer of Plant Domestication Giora Simchen2. The Use of Association Genetics Approaches in Plant Breeding María F. Álvare, Teresa Mosquera, and Matthew W. Blair 3. Epigenetics Connects the Genome to its Environment Ray A. Bressan, Jian-Kang Zhu, Michael J. Van Oosten, Hans J. Bohnert, Viswanathan Chinnusamy, and Albino Maggio 4. Peanuts Improvement for Human Health Sangam Dwivedi, Naveen Puppala, Soheila Maleki, Peggy Ozias-Akins, and Rodomiro Ortiz5. Rice Breeding.